Passing of Risk under CISG and Incoterms 2020 Rules: Legal framework and Contractual Autonomy - Gorenc, Nastja (LeXonomica, 2026)
This article examines the relationship between CISG and Incoterms as key instruments regulating international sales contracts. Both frameworks reflect party autonomy, enabling parties to adapt contractual terms to the needs of modern global trade. CISG applies by default to international sales contracts under Art. 1 CISG, unless expressly excluded, while Incoterms apply through contractual incorporation or established usage. The article examines that Incoterms do not replace CISG but function alongside it, particularly regarding delivery and transfer of risk. Because Incoterms connect risk transfer to logistical events and CISG relies on legal criteria, inconsistencies may cause disputes when contracts are poorly drafted. In such cases, courts and tribunals interpret the parties’ agreement through Arts. 8, 9 CISG rather than redefining obligations. The article emphasizes that, despite some ambiguities in CISG’s risk provisions, it remains a major achievement in harmonizing international sales law. When combined with Incoterms, it provides a more effective framework for allocating risk and responsibilities. The article concludes that disputes are best avoided through clear drafting that regulates CISG’s role, the relevant Incoterms rule, and defines the parties’ obligations. Povzetek članka v slovenskem jeziku (abstract in Slovene language): Članek obravnava razmerje med CISG in Incoterms kot ključnima instrumentoma mednarodne prodaje blaga. Oba odražata avtonomijo strank, saj omogočata prilagoditev pogodbenih določb potrebam konkretnega razmerja in zahtevam sodobne svetovne trgovine. CISG se na podlagi 1. člena CISG uporablja za mednarodne prodajne pogodbe, razen če je izrecno izključen, Incoterms pa veljajo, kadar se stranki nanje sklicujeta izrecno ali molče. Avtorica analizira njuno razmerje in medsebojni vpliv ter poudarja, da Incoterms CISG ne nadomeščajo, temveč ga dopolnjujejo, zlasti glede izročitve in prehoda nevarnosti naključnega uničenja, izgube ali poškodovanja blaga s prodajalca na kupca. Ker Incoterms prehod nevarnosti vežejo na logistične dogodke, CISG pa na pravna merila, lahko nejasne pogodbene določbe povzročijo spore. V takih primerih sodišča določbe in namen strank razlagajo v skladu z 8. in 9. členom CISG. Avtorica poudarja, da CISG kljub nekaterim dvoumnim ali splošnim določbam o prenosu rizika ostaja pomemben dosežek na področju harmonizacije mednarodne prodaje blaga. Skupaj z Incoterms zagotavlja učinkovitejši okvir za presojo tveganj in odgovornosti. Stranke naj v izogib nejasnostim in morebitnim sporom pogodbe oblikujejo jasno in določno ter natančno opredelijo uporabo klavzul Incoterms in obveznosti po CISG.